Integrasi FOMO dan Literasi Keuangan dalam Membentuk Model Keputusan Investasi IPO yang Lebih Rasional - Khomisatul Fitri; Asmaul Layli; Nuzul Fatiha; Tasya Tasya; Joni hendra (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
The growing participation of retail investors in Initial Public Offerings (IPOs) indicates that investment decisions are shaped not only by rational analysis but also by psychological dynamics such as FOMO, which arises from social pressure, market euphoria, and fear of missing potential gains. This study aims to examine how FOMO influences impulsive decision-making in IPO investments and how financial literacy mitigates this influence, ultimately shaping more rational investment behavior. This research employs a literature review approach, collecting data from national and international journals, official financial institution reports, and relevant academic publications, which were then analyzed using content analysis to identify conceptual patterns and variable relationships. The findings reveal that FOMO strongly drives impulsive behavior, particularly among investors with low literacy levels, while financial literacy functions as a cognitive regulator that reduces impulsivity and enhances decision quality. The study concludes that the integration of FOMO and financial literacy forms the IPO Rationality Model, offering a new conceptual framework for understanding modern investment behavior and providing practical implications for investor education, regulatory policy development, and risk-mitigation features in digital investment platforms